CHOLESTEROL ESTERS OF SHEEP WOOL UNDER THE INFLUENCE OF BIODEGRADATION BY FLEECE MICROORGANISMS - Tkachuk , В.; Ohorodnyk , Н.; Motko , Н.; Pavkovych , С.; Ratskyi , М.; Kozak , Р.; Dudar , І. (Bulletin of Lviv National Environmental University. Series Agronomy, 2025)
Sheep fleece is an ideal environment for the growth and development of microflora, as it provides optimal conditions – heat, air, moisture, and also serves as a substrate – grease and keratin of the wool itself. In this regard, cholesterol esters of surface and internal lipids of sheep wool under the influence of biodegradation by microorganisms were studied. The research focused on damaged wool samples from Ascanian fine-wool ewes with high microbial contamination, while the control group consisted of undamaged wool with low microbial levels. Surface lipids (wax) were obtained by extraction in a Soxhlet apparatus with tetrachloromethane, free internal lipids were obtained through repeated extraction with a chloroform–methanol mixture (2:1), and bound internal lipids were obtained after prior alkaline hydrolysis. Cholesterol esters were separated in the n-heptane–toluene (8:2) system, being represented by six classes in surface lipids and four classes in internal wool lipids. It was found that the cholesterol of the wax of damaged wool is characterized by a lower content of esters of saturated acids – 36.13 % (P < 0.001), compared with 41.39 % in wool in normal condition; and a higher content of unsaturated and, especially, trienoic acids – 5.83 vs. 4.53 % (P < 0.05) and tetraenoic acids – 5.91 vs. 4.81 % (P < 0.05). The free internal lipids of damaged wool contain a lower content of saturated acid esters (P < 0.001), and a higher content of di-, tri-, and tetraenoic (P < 0.05) and other polyenoic (P < 0.001) acids. The esterified cholesterol of the bound internal lipids of defective wool contains a smaller amount of saturated esters and, especially, monounsaturated acids 15.13 % (P < 0.05), compared to 17.58 % in wool in normal condition. In contrast, in damaged wool there is a larger amount of di-, tri-, and tetraenoic (P < 0.05) and other polyenoic (P < 0.01) esters. Such changes indicate the presence of hydrolytic processes occurring in the environment of the grease and internal lipids of the wool, which ultimately can have a negative effect on the structure of wool fibers and, above all, their cuticular layer.